1976
DOI: 10.1161/01.cir.53.5.802
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular function and adrenergic hyperactivity before and after saphenous vein bypass.

Abstract: Forty patients with severe angina pectoris were studied before and two weeks after saphenous vein bypass surgery (SVG) in order to assess the effect of this operation on left ventricular performance as judged by systolic time intervals (STI). The patients were divided into two groups: group I included 29 patients in whom no postoperative infarction occurred and group II was composed of 11 patients with postoperative infarction. For group I the PEP/LVET was 0.39 +/- 0.01 preop and slightly but significantly inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1979
1979
1985
1985

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The PEPIL VET was not different in both groups before and two weeks after surgery, and was mildly but significantly increased. Patients with peri operative infarction were exluded from this analysis, since it is known that peri-operative infarction produces a significant deterioration in left ventricular performance (4,8,10,20,24,25).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PEPIL VET was not different in both groups before and two weeks after surgery, and was mildly but significantly increased. Patients with peri operative infarction were exluded from this analysis, since it is known that peri-operative infarction produces a significant deterioration in left ventricular performance (4,8,10,20,24,25).…”
Section: Resultsmentioning
confidence: 99%
“…Postoperative decrease in left ventricular function as measured from the systolic time intervals two weeks after surgery was mild and identical in both groups. Of note, we excluded patients with perioperative myocardial infarctions from this analysis since myocardial infarction produces a significant deterioration in left ventricular performance (8,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ischemic injury to the myocardium during bypass surgery has been repeatedly demonstrated from a spectrum of clinical evidence (Sung el al., 1977;Boudoulas et al, 1976). A significant incidence of perioperative myo cardial infarction (Dixon et al, 1973;Oldham et al, 1973;Righetti/et al, 1977a).…”
Section: Discussionmentioning
confidence: 99%
“…There have been relatively few studies examining changes in preoperative and postoperative perfusion as provided by individual coronary artery bypass grafts.27 28 Furthermore, even though numerous studies have shown that bypass grafts will provide significant relief of angina in 75-80% of patients who undergo surgery,', 29 the effectiveness of this procedure in improving left ventricular function remains controversial. [29][30][31][32][33][34][35][36][37][38][39][40][41][42] In this study we investigated the significance of preoperative perfusion defects and left ventricular contraction abnormalities in patients with unstable angina by measuring the effects of coronary artery bypass surgery upon reversing such perf-usion and contraction abnormalities and relating the results of surgery to the clinical response. …”
mentioning
confidence: 99%